Efektivitas Model Sport Education dalam Pembelajaran Pendidikan Jasmani di Sekolah Dasar: Systematic Literature Review - Saeful Rohman; Rama Wijaya Abdul Rozak; Atep Sujana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to examine the efectiveness of the Sport Education Model (SEM) in improving Physical Education learning outcomes at the elementary school level compared to traditional teaching approaches, as well as to identify optimal implementation characteristics and existing reaserch gaps. The study employed a Systematic Literature Review design following the PRISMA 2020 guidelines. A comprehensive literature search was conducted in the Scopus database in Januari 2026, covering publication from 2020 to 2026. After a rigorous multi-stage screening process, 33 eligible articles were included in the final synthesis, with 15 studi incorporated  into a meta-analysis. The findings revealed that SEM demonstrated a statistically significant overall effec size of 0.590 (p < 0.001), indicating a moderate to large impact compared to traditional instruction. The stronges effects were observed in the effective and social domain (0.612), followed by cognitive (0.589) and psychomotor (0.471) outcomes. Optimal implementation characteristics included a season based structure, two sessions per week with a minimum duration of 60 minutes, and comprehensive teacher training support. Despite the strong empirical support, further longitudinal reaserch, expanded studies in developing countries, and investigations into gender differences and cost-effectiveness are recommended to strengthen the generalizability and practical implication of SEM implementation.   Keywords: Elementary School; Learning Outcomes; Physical Education; Sport Education Model.